Sinergi Pendidikan Islam antara Sekolah dan Orang Tua dalam Meningkatkan Mutu Lulusan - Halimatus Sa'diyah; Irma Nur Hayati (CV Kalimasada Group, 2025)
This research focuses on the synergy between teachers and parents in shaping the character and discipline of early childhood students at TK Nurul Huda. Early childhood is a critical period for emotional and intellectual growth, where both parental and educational roles are essential in instilling values such as discipline and good behavior. The study reveals that cooperation between teachers and parents plays a crucial role in developing discipline and academic skills such as reading, writing, and counting. The findings highlight various strategies for strengthening this partnership, including setting shared educational goals, fostering effective communication, and engaging parents in school activities. The research also identifies supporting and hindering factors in building a strong synergy, such as the availability of communication tools and the level of parental awareness regarding the importance of discipline. This study emphasizes the importance of a collaborative approach between teachers and parents in achieving quality educational outcomes for young learners.